RANCANG BANGUN APLIKASI PENJUALAN TERNAK BUMDes BERBASIS WEBSITE - Jadiaman Parhusip; Akhmad Kamilen (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2021)
BUMDes is a rural-based business organization managed by the local government. One of the businesses managed by them is the livestock business. The pandemic of Covid-19 affects the uncertainties of marketing, including the livestock sector. To avoid failing, an innovative and effective marketing effort needs to be expanded. One of ways is selling through the website. The research methodology that was used in developing this website is waterfall. This research was started by deciding the scope of the research location, formulating the problems, and deciding the method. Digging out the problem was done by conducting some in-depth interviews with the management of BUMDes, studying literature, and conducting field observation. The website of BUMDes is equipped with useful features such as admin, customer, login, category, searching, shopping cart, payment confirmation, ordering details, shipping fee, etc. All the usages of those features had been tested using Blackbox testing method and were proclaimed to be successful or ready to use. Besides the star scheme, the snowflake scheme needs to be utilized for the basis data for future development. The use of snowflake scheme is used to anticipate the expansion of the marketing area as well as possibility of the increasing number of breeders joining the BUMDes